Analysis of Ignition Capability of Flammable Gases from Small Arms Propellant Gases - Przemysław BADUROWICZ; Adam WIŚNIEWSKI; Marcin JASIŃSKI; Dawid PACEK; Krzysztof SZCZUROWSKI; Marek WOLIŃSKI; Tadeusz BARTKOWIAK (Problemy Mechatroniki)
The article presents the results of tests on the temperature of propellant gases shortly after the bullet leaves the barrel. The temperature and movement of these gases were recorded with thermal cameras and a high-speed camera. Weapons with and without muzzle devices (flash suppressor, silencer) were used. The aim of the research was to check the capability to ignite flammable gases located in the vicinity of the propellant gases produced during firing. Comparison of the maximum temperature of the propellant gases and the ignition temperature of the flammable gases makes it possible to determine the probability of fire. The lowest temperature of propellant gases was in the case of shooting with 9 19 mm bullets with the lowest kinetic energy (518 J), and the highest temperature of these gases was during shooting with 5.56 45 mm HC (SS109) bullets with the highest kinetic energy (1,785 J).